STRATEGI PEMENUHAN KEBUTUHAN PANGAN (PADI) DI KABUPATEN ROKAN HULU - Yariana Adi Ratna Putra; Harlen Harlen; Hendro Ekwarso (Program Studi Pendidikan Ekonomi Universitas Riau, 2021)
The main objective of this research is to identify strategies for meeting the needs of food in Rokan Hulu Regency. The research was conducted in Rokan Hulu Regency, Riau Province, which is one of the 12 districts / cities in Riau Province. The data used in this research is secondary data. Secondary data are supporting data that have been published and obtained from books, magazines, etc. related to this research. In the research on the Strategy of the Department of Agriculture and Food Security in improving Food Security in Rokan Hulu Regency, the theory used is the SWOT analysis theory.Based on the research results, it is known that Rokan Hulu Regency in facing threats and opportunities is still not good. The most significant threats at this time are dependence on imports and the powerlessness of the government to eradicate the food mafia and cartel practices which have had a sustainable impact on price increases, food scarcity, state economic conditions, and the credibility of the people towards their own government. On the other hand, the opportunity for Rokan Hulu Regency to advance food security lies in its very broad geographical factors. However, these potentials to become the driving force for national food are still not being maximized due to limited access to infrastructure, distribution, research and development, and qualified human resources. food security management in Rokan Hulu Regency is still not good enough. The most major strengths can be seen in the decision-making process, namely the need for budgeting and stability of economic policies to meet strategies to strengthen food security. Meanwhile, the most significant weakness lies in the human resource factor or farmer actors, namely the low level of farmer income and the decline in the preference of the agricultural sector as a source of community income which affects the choices of farmers to be productive and advanced due to the lack of incentives and training for farmers.